Disclosure and Help-Seeking Experiences of Sexual and Gender Minority Victims of Intimate Partner Violence: A Mixed-Methods Study - Whitton, Sarah W. (Journal of interpersonal violence, 2024)
Sexual and gender minorities assigned female at birth (SGM-AFAB) experience high rates of intimate partner violence (IPV), with negative effects on health and well-being. Disclosure of and help-seeking for IPV can support the well-being of IPV survivors, yet are understudied among SGM-AFAB people. To better understand the IPV disclosure and help-seeking experiences in this population, we conducted semi-structured interviews with 41 SGM-AFAB young adults who experienced physical, sexual, or severe psychological IPV. Qualitative analyses explored to whom SGM-AFAB disclosed IPV, barriers to disclosure/help-seeking, the types of responses received, and perceived helpfulness of responses. Exploratory mixed methods analyses assessed frequency of code endorsement, demographic differences, and associations among codes. Three-quarters of participants disclosed IPV, though rates were lower for sexual and physical than psychological IPV and very few sought help from formal sources. The most common barriers to disclosure were not viewing the IPV as abuse and anticipation of negative responses, often due to stigma; other participants described inability to access formal help and concerns about SGM incompetence in those services. Most actual responses received were considered helpful, including emotional support, labeling the IPV as unhealthy, nonjudgmental listening, actions to stop the IPV, and practical support. Minimizing IPV or criticizing the victim was common unhelpful response; advice to end the relationship was considered helpful and unhelpful. Whereas 92% of friend responses were described as helpful, around half of family (56%) and therapist (62%) responses were helpful. Findings suggest that efforts to increase access to culturally affirmative services and educate SGM youth to recognize IPV in their relationships may help promote help-seeking and well-being among SGM-AFAB IPV survivors.